Impacts of Climate Change on Stream Flow in the Gomti River Basin of India - Abeysingha, N. S.; Singh, Man; Islam, Adlul; Khanna, Manoj; Sehgal, V. K.; Pathak, H. (Journal of Agricultural Engineering, 2018)
Potential impacts of climate change on streamflow in the Gomti River basin of India were studied using the Soil and Water Assessment Tool (SWAT) model. The model was calibrated and validated using monthly streamflow data of four gauging stations of the basin. Climate change scenarios were developed using spatially downscaled (0.5Ã—0.5Â°) MIROC3.2 (HiRes) GCM data for A2, A1b and B1 emission scenarios. The analysis showed that annual rainfall is likely to increase by 10 % to 18 %, 15 % to 24 %, and 19 % to 26 % during the 2020s, 2050s and 2080s, respectively. Mean annual stream-flows were projected to increase by 15 % to 38 %, 25 % to 44 % and 40 % to 55 % during the 2020s, 2050s and 2080s, respectively. Simulation results also indicated spatial and temporal variability in stream-flow in the basin, indicating the need for location-specific adaptation measure for planning of water use in the basin. The findings of the study could be useful for planning and managing water resources in the Gomti river basin for adaptation to climate change.